Kelengkapan Informasi Medis Dalam Penetapan Kode Morbiditas, Pada Kasus Chronic Kidney Disease Di Rumah Sakit Panti Wiloso Dr Cipto Semarang - Dyah Ernawati; Laurensia Rossandra (Dian Nuswantoro Semarang, 2020)
Observations were made on the medical record documents of the Chronic Kidney Disease (CKD) case, found incomplete medical information, namely the results of X-rays of 70%, other tests of 20%, writing of disease history of 10% and some of the stages of disease were not written. The results of the interview with one of the coders were due to the lack of accuracy in filling in medical supporting data. The aim of the study was to describe the medical information in determining morbidity coding in CKD cases.Using a quantitative descriptive research approach, data from observations of 63 documents of CKD inpatient medical records were completed with information from one of the inpatient coder officers.The results showed that, there was still incomplete medical information such as the results of investigations and medical history. And several documents were found whose examination result sheets were not in DRM. The procedure for determining the code in the RS Panti Wilasa Dr Cipto in the CKD case did not differ in giving morbidity codes with other cases. The flow is in accordance with the implementation guidelines for coding in ICD 10 Revision 2010. However, in determining the code the main obstacle is the lack of clarity in writing medical diagnoses, and there is an incomplete history. The conformity of the morbidity code based on ICD-10 version 2010 in the case of CKD in Dr Cipto Panti Wilasa Hospital was 71.42% and the code mismatch was 28.58%. This is due to incomplete medical information and unclear stages of CKD disease.It is advisable for the coder to confirm to the DPJP if there is a diagnosis that is illegible or less specific so that the code generated is appropriate and precise, especially in the diagnosis of CKD. The need to complete medical information and double-check medical record documents before coding.Keywords: Medical Record Documents, Chronic Kidney Diseases, Morbidity Code, ICD-10